2000
DOI: 10.1161/01.cir.102.8.846
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cholesterol-Lowering Therapy on Coronary Endothelial Vasomotor Function in Patients With Coronary Artery Disease

Abstract: Six months of cholesterol-lowering therapy has no significant effect on coronary endothelial vasomotor function in the study population of patients with coronary artery disease and mildly elevated cholesterol levels. These findings suggest that the effects of cholesterol lowering on endothelial function are more complex than previously thought.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
1
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(76 citation statements)
references
References 27 publications
3
71
1
1
Order By: Relevance
“…Similar to our findings, another study showed that 6 months of cholesterol-lowering therapy had no significant effect on coronary endothelial vasomotor function in a population of patients with CAD and mildly elevated cholesterol levels. 23 In that study, the authors also suggested the reason for the lack of improvement in endothelial function was attributable to a lower baseline LDL-C level and the mild degree of CAD. Therefore, these findings support the importance of adequate statin treatment for primary prevention.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Similar to our findings, another study showed that 6 months of cholesterol-lowering therapy had no significant effect on coronary endothelial vasomotor function in a population of patients with CAD and mildly elevated cholesterol levels. 23 In that study, the authors also suggested the reason for the lack of improvement in endothelial function was attributable to a lower baseline LDL-C level and the mild degree of CAD. Therefore, these findings support the importance of adequate statin treatment for primary prevention.…”
Section: Discussionmentioning
confidence: 94%
“…Additionally, the proportion of subjects who normalized endothelial function (RHI ≥2) after atorvastatin and placebo treatment was not significantly different (40% vs 37%, P = 1.000) (Figure 3). The augmentation index after atorvastatin treatment was not different from that after placebo treatment (24 [IQR, [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] vs 29 [IQR 16-35], P = 0.922). In the subgroup analysis, these results were consistent both in subjects indicated for drug therapy (11 subjects, 31%) and subjects not indicated for drug therapy (24 subjects, 69%), according to the NCEP-ATP III guidelines.…”
Section: Resultsmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14] What this study adds Pravastatin 40 mg daily did not reduce blood pressure or pulse pressure at any time point in 4126 survivors of myocardial infarction who were followed for more than 5 years.…”
mentioning
confidence: 73%
“…6 For instance, statins reduce markers of inflammation such as C-reactive protein, 7 and may reverse endothelial dysfunction through their effects on nitric oxide synthase 8 or by other mechanisms, 9 although this is controversial. 10 Since these abnormalities are associated with hypertension, it is plausible that statin therapy might also reduce blood pressure. 11,12 Several previous experimental and retrospective studies suggest that statins reduce blood pressure in animals and humans with and without hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Thus, improved endothelium-dependent dilator responsiveness after statin therapy, demonstrated by provocative testing and clinically manifest as reduced ischemia during stress, has been viewed widely as a useful mechanistic surrogate for reduced cardiovascular risk by that therapy. However, in this issue of Circulation, 10 investigators of the Coronary Artery Reactivity After Treatment with Simvastatin (CARATS) study found no benefit of simvastatin 40 mg/d for 6 months to coronary artery epicardial or microvascular endothelial vasodilator function in 34 analyzable patients with mild to moderate coronary artery disease randomly assigned to this therapy, compared with 26 analyzable patients randomized to placebo in a double-blind clinical trial. Participants were mildly hypercholesterolemic (average LDL cholesterol 130 mg/dL) and had not been on cholesterollowering therapy for at least 6 weeks before study.…”
Section: See P 846 Endothelial Vasodilator Function Testing Myocardimentioning
confidence: 98%